Proceedings of the 7th ACM International Conference on Web Search and Data Mining 2014
DOI: 10.1145/2556195.2556251
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the impacts of social media on crowdfunding

Abstract: Crowdfunding -in which people can raise funds through collaborative contributions of general public (i.e., crowd) -has emerged as a billion dollars business for supporting more than one million ventures. However, very few research works have examined the process of crowdfunding. In particular, none has studied how social networks help crowdfunding projects to succeed. To gain insights into the effects of social networks in crowdfunding, we analyze the hidden connections between the fundraising results of proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
2
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(160 citation statements)
references
References 23 publications
6
144
2
8
Order By: Relevance
“…He also pointed out that the project financing duration negatively affect the financing success rate, because longer period of investment will reduce enthusiasm for the investment [7]. Many researchers found that the impact of the target amount on financial performance on project success rate is negative [8][9][10][11][12]. Some found that the impact of the number of projects initiated and updates on financial performance has positive effects [8,10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…He also pointed out that the project financing duration negatively affect the financing success rate, because longer period of investment will reduce enthusiasm for the investment [7]. Many researchers found that the impact of the target amount on financial performance on project success rate is negative [8][9][10][11][12]. Some found that the impact of the number of projects initiated and updates on financial performance has positive effects [8,10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Crowdfunding project characteristics refer to the project attributes that relate to the funding decision. These attributes are reputation of initiator [29], popularity of crowdfunding project [51], and crowdfunding project content quality [59].…”
Section: Environmental Cuesmentioning
confidence: 99%
“…Analysis studies aimed to determine how updates about the campaign affect the result of the campaign in the process of campaign (Xu et al, 2014); qualitative studies aimed to search effects of internal social capital on the campaign (Colombo et al, 2015); researches aimed to determine the effects of the creator of the campaign on the campaign (Wojciechowski, 2009); the effects of individual and aggregate studies on the campaign (Hui et al, 2014); studies aimed to determine the effects of social media on crowdfunding (Lu et al, 2014). It can be seen that the studies generally focus on searching success and effect level of the campaign when these studies are analysed.…”
Section: Related Workmentioning
confidence: 99%